Rosmarinus officinalis essential oil triggers depression followed by CNS excitability in Wistar rats - Bastos de Araújo, Daniella; Raiol de Almeida, Ysis Nayhara; Otake Hamoy, Maria Klara; Vasconcelos de Souza, Luana; Pacheco Hartcopff, Priscille Fidelis; Gonçalves dos Santos, Rodrigo; Santos da Silva, Lívia Letícia; Lima da Rocha, Lucas; Farias dos Santos, Murilo; da Silva Deiga, Yris; da Cunha Ferreira, Rayllan; Vieira de Souza, Raíssa; et al. (Frontiers in Natural Products, 2024)
Rosemary essential oil (Rosmarinus officinales) is widely used in folk medicine 10. and has proven therapeutic effects. Our research evaluated high doses of Rosemary 11. essential oil in Wistar rats. Fifty-four male rats between 180 and 200g were used. The 12. present article was divided into three experiments: (1) Behavioral monitoring of the 13. animals after administration of 500 mg/kg i.p., (2) Electrocorticographic records 14. after drug administration and (3) Anticonvulsant drug reaction, where were applied 15. Phenytoin, Phenobarbital and Diazepam 10 mg/kg i.p. The results showed that the application 16. of rosemary oil, presented two phases. Phase 1 was characterized by the appearance of 17. myorelaxation and a reduction in the power of the electrocorticogram in low-frequency 18. cerebral oscillations. Phase 2 was characterized by increased excitability, with the 19. appearance of convulsions and increased power of electrocorticographic recordings in cerebral 20. oscillations up to 40 Hz. In this phase, three tracing patterns were observed. Beta 21. oscillations were the most prevalent and were better controlled by Diazepam, which 22. demonstrates that the excitatory activity of Rosmarinus officinalis essential oil is related to 23. the reduction of GABAergic activity.